Optimization of Early Antimicrobial Strategies for Lung Transplant Recipients Based on Metagenomic Next-Generation Sequencing - Zhang, Xiao-qin; Lei, Yu; Tan, Xiao-li; Guo, Lu; Huang, Xiao-bo; Yang, Fu-xun; Yu, Hua; Liu, Xiao-shu; Wang, Yi-ping; Lu, Sen; Pan, Ling-ai (Frontiers in Microbiology, 2022)
The management of perioperative antibiotic options after lung transplantation varies widely around the world, but there is a common trend to limit antibiotic use duration. Metagenomic next-generation sequencing (mNGS) has become a hot spot in clinical pathogen detection due to its precise, rapid and wide detection spectrum of pathogens. Thus, we defined a new antibiotic regimen adjustment strategy in the very early stage (within 7 days) after lung transplantation mainly depending on mNGS reports combined with clinical conditions to reduce the use of antibiotics. To verify the clinical effect of the strategy, we carried out this research. 30 patients who underwent lung transplantation were finally included, whose information including etiology, antibiotic adjustment, and the effect of our strategy was recorded. Lung transplant recipients in this study were prescribed with initial antibiotic regimen immediately after surgery, their antibiotic regimens were adjusted according to the strategy. According to our study, the entire effectiveness of the strategy was 90.0% (27/30). Besides, a total of 86 samples containing donor lung tissue, recipient lung tissue, and bronchoalveolar lavage fluid (BALF) were obtained in this study, they were all sent to mNGS test, while BALF were also sent to pathogen culture, their results showed that the positive rate of BALF samples was higher (86.67%) than that of donor’s lung tissue (20.0%) or recipient’s lung tissue (13.33%) by mNGS test, indicating BALF samples are more valuable than other clinical samples from early postoperative period to guide the early adjustment of antibiotics after lung transplantation. It is effective for mNGS combined with traditional methods and clinical situations to optimize antibiotic regimens in lung transplantation recipients within 7 days after surgery.